Optimal Resource Allocation to Enhance Power Grid Resilience Against Hurricanes - Yang, Zejun; Marti, Andrea; Chen, Ying; Marti, Jose R. (IEEE transactions on power systems, 2023)
Optimal resource allocation is critical when maximizing the resilience of the electrical power distribution network against natural disasters. This paper presents a two-step optimization strategy that integrates a pre-disaster preparedness plan and a post-disaster resource re-allocation procedure to optimize the resilience of the power distribution network against hurricanes. Emergency resources are operationally interdependent, and it is these interdependencies that determine how the resources should be distributed to the critical loads in the network. This work uses the concept of the Human Readable Table (HRT) to relate the interdependencies among these resources. The resource allocation optimization is then formulated into a Mixed-Integer Nonlinear Programming (MINP) problem. The proposed method is tested on the IEEE 70-node system. The results show that this two-step procedure decreases the probability of failure for the critical nodes during the pre-hurricane stage and increases the system's ability to recover during the post-hurricane stage.